2022
DOI: 10.1007/s10639-022-11258-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impacts of learning modality changes: Validation of the learning modality change community of inquiry and self-efficacy scales

Abstract: The rapid learning environment transition initiated by the COVID-19 pandemic impacted students’ perception of, comfort with, and self-efficacy in the online learning environment. Garrison’s Community of Inquiry framework provides a lens for examining students’ online learning experiences through three interdependent elements: social presence, cognitive presence, and teaching presence. Researchers in this study developed and validated the Learning Modality Change Community of Inquiry and Self-Efficacy scales to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The measurement constructs included self-efficacy, attitudes towards remote learning online, teaching presence, social presence, and cognitive presence. The 29-item instrument was found to have strong construct validity [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement constructs included self-efficacy, attitudes towards remote learning online, teaching presence, social presence, and cognitive presence. The 29-item instrument was found to have strong construct validity [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…The overall cross-sectional study design analyzed self-reported data collected in the CoI instrument [ 61 ]. The questionnaire and methodology for this study was first approved by Louisiana State University Health Sciences Center University Institutional Review Board, then subsequently approved by the boards at participating institutions.…”
Section: Methodsmentioning
confidence: 99%
“…The measurement constructs included self-e cacy, attitudes towards remote learning online, teaching presence, social presence, and cognitive presence. The 31-item instrument was found to have strong construct validity (Jia et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…I feel con dent in...". The revised 11 item scale (Jia et al, 2022) based on two existing self-e cacy scales in the literature, has been validated in a con rmatory factor analysis in a similar student sample. The overall internal reliability was 0.95.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation